Biosynthesis and optimization of methyl 3-(3,5- di-tert-butyl-4-hydroxyphenyl) propionate production from oil palm frond juice by ceratocystis fimbriata - Nang Nor Azimah, Long Nadzri (2018)
In Malaysia, oil palm plantations and the palm oil industries were the main contributors to the generation of agricultural waste. From previous studies, researchers have identified the potential of utilizing the agricultural waste efficiently. In this research, oil palm frond (OPF) juice was used to replace the function of glucose during fermentation. OPF juice is reported to contain renewable sugars such as glucose, sucrose and fructose. OPF juice is expected to address the environmental issues to produce volatile organic compounds (VOCs) especially for production of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate as OPF is abundantly available as a biomass and easily available throughout Malaysia. The utilization and development of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate production fungus have been of increasing interest as they are naturally produced without chemical synthesis. Ceratocystis fimbriata is a fungus which has the potential for synthesizing esters, it grows quickly and produces a variety of aromas (peach, pineapple, banana, citrus and rose) depending on the strain and culture conditions. The aim of this study was to screen and optimize methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate using a series of experimental design by a head space-solid phase micro extraction (HS-SPME) technique combined with gas chromatography-mass spectroscopy (GC–MS) was used to separate the relative peak area of the compound during the fermentation. Optimization of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate production are affected by several factors during the period of fermentation. Series of experimental designs were applied to screen and optimize the production of the compound. In the screening study, 24 full factorial design were used to find significant factors affecting production of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, which are incubation temperature (25 °C-35 °C), initial pH medium (pH4, pH8), agitation speed (100 rpm, 150 rpm) and concentration of glucose (20 g/L, 30 g/L) in OPF juice. The responses in screening were fitted with a multiple linear regression equation and obtained a correlation (R² = 0.8960) between the experimental data and model data. Then central composite design (CCD) was applied as the experimental design and a polynomial regression model with quadratic term was used to analyze the experimental data using analysis of variance (ANOVA). ANOVA analysis showed that the model was very significant (p < 0.0001) for the methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate production. The responses were fitted with the second order polynomial equation with high correlation (R² = 0.9598) between the observed and predicted values. The results of optimization process showed that a maximum methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate production was obtained under the condition of initial pH medium (8), agitation speed (100 rpm) and incubation temperature (25°C). Under these optimized conditions, the highest 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate production was obtained when the column retention time was 32.80 minutes and the relative peak area was 0.29 % of chromatogram area by using GC-SPME. As a conclusion, this study provides a significant guideline and basic of understanding for the production of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate compound at larger scale using OPF juice as sole, renewable and sustainable substrate by C. fimbriata in the near future.